Comment on: Price Discovery in High Resolution. (15th March 2019) - Buccheri, Giuseppe; Bormetti, Giacomo; Corsi, Fulvio; Lillo, Fabrizio
Abstract: This note is commenting on Hasbrouck (2018). The paper investigates the problem of price discovery on markets with trades recorded at sub-millisecond frequencies. The application of the popular information share measure of Hasbrouck (1995) to such data faces several difficulties, as the underlying vector error correction models would need a huge number of lags to capture dynamics at different time-scales. The problem is handled by imposing a set of restrictions on parameters inspired by the Heterogeneous Autoregressive model for realized volatility. We illustrate some potential drawbacks of the information share measure adopted in the paper and propose a modeling strategy aimed at dealing with such limitations. In particular, we introduce a structural multi-market model with a lagged adjustment mechanism describing lagged absorption of information across markets. The advantages of the method are shown in simulations.